TRADITION, MODERNITY, AND SOCIAL ADAPTATION: ANTHROPOLOGICAL INSIGHTS INTO CHANGING SOCIAL STRUCTURE - Emmy Solina; José González; Marta López (Cognitionis Civitatis et Politicae, 2025)
The tension between persistent cultural traditions and the relentless onset of global modernity represents a fundamental challenge for contemporary social structures. This research addresses the problem of structural fragmentation and “cultural lag” in traditional societies as they navigate the pressures of rapid urbanization and digital connectivity. The study aims to evaluate the mechanisms of social adaptation and the renegotiation of kinship authority within transitioning communities. Utilizing a multi-sited ethnographic methodology, the research integrated participant observation and semi-structured interviews across rural ancestral homelands and urban migrant settlements. Results demonstrate that traditional social structures are undergoing a process of “re-functionalization” rather than simple erosion, with a 66% surge in digital kinship maintenance serving as a vital bridge for trans-local sociality. Findings indicate that while physical households are nuclearizing, traditional authority persists through the hybridization of meritocratic status and hereditary lineage. This research concludes that social adaptation is a proactive negotiation where tradition functions as a strategic resource for navigating modern precarity. The study provides a scalable blueprint for “culturally-embedded” policy design, asserting that the future of social resilience lies in the successful synthesis of inherited ontological security and modern technological tools.